Tinhorn : Heat Lightning - Book 3 - Johnstone, William W.; Johnstone, J.A. (New York : Pinnacle Books/Kensington Publishing Corp., 2022)
"To wealthy rancher Ira Dunellen, the frontier prairie land surrounding his spread is his for the taking. His cattle need room to roam and the one-horse town of Tinhorn, Texas is standing in his way. On the bank of the Neches River, the small community of merchants is just wasting a precious resource that Dunellens growing range needs. As stray cattle wander into town, followed by rowdy cowboys, Sheriff Flint Moran and partner Buck Jackson start corralling up any man or beast disrespecting the citizenry and breaking the law. Its clear Tinhorns lawdogs are doing their jobs a little too well, so Dunellen hires deadly gunslinger Cash Kelly to put the blast on them--all the way to Boot Hill. But unknown to Dunellen, Cash Kelly has his own reasons why he wants Flint Moran dead. Bullets will fly. And the dusty street of Tinhorn will be awash in blood..." -- Page [4] cover
Keywords: Cattle -- Fiction; Gunfighters -- Fiction; Ranchers -- Fiction; Sheriffs -- Fiction; Texas -- Fiction; Action and adventure fiction; Western fiction